Short-term return-based contrarian strategies in international interest rates futures : 1993-2002 - Goon, Hui Wern (2008)
In this thesis, we document return reversals and investigate profitability of contrarian strategies in international interest rate futures markets. For the analysis, we construct a methodology vy closely following the spirit behind the Lo and Mackinlay (1990) methodology developed for contrarian strategy in equity market.